The Freedom of Association Mess: How We Got into It and How We Can Get out of It - Langille, Brian (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractCanadian constitutional law regarding freedom of association for workers is a mess. The jurisprudence to date has taken an approach to state action and positive obligations to legislate which is inconsistent with section 15, and has failed to articulate the relationship between the abstract statement of basic rights or freedoms and the detailed statutes and regulations that instantiate and enforce them. This paper focuses on the impact of the recent decision of the Supreme Court of Canada in BC Health. The author argues that this case misunderstood Canada’s labour law history, international labour law obligations, “Charter values”, and the distinction between “freedoms” and “rights”.This paper argues that by using labour relations statutes as a starting point and applying the constitutional idea of equality, courts can protect freedom of association for workers and find a way out of the mess we are in.